Judicial Review Of Parliamentary Oversight on The Issuance of the Job Creation Emergency Law from the Check and Balances Perspective - Firna Dwi Ananda; Muhamad Aksan Akbar; Syamsul Rijal (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2026)
This study aims to analyze the mechanism of the implementation of the House of Representatives (DPR) oversight function towards the issuance of Government Regulation in Lieu of Law (Perppu) based on the 1945 Constitution and evaluate the application of the principle of checks and balances in the procedure of issuance and approval of Perppu Number 2 of 2022 concerning Job Creation into Law Number 6 of 2023. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach. The results of the study indicate that normatively, the 1945 Constitution has explained a strong mechanism of checks and balances where the DPR acts as a constitutional gateway through its legislative and supervisory functions to test the President's subjectivity regarding the parameters of